2020
DOI: 10.3389/fonc.2020.584917
|View full text |Cite
|
Sign up to set email alerts
|

FIGO Stage IV and Age Over 55 Years as Prognostic Predicators in Patients With Metastatic Malignant Struma Ovarii

Abstract: Introduction: Metastatic malignant struma ovarii (MSO) is an extremely rare disease that lacks treatment consensus and accurate prognosis. The objective of this study was to present the clinical, pathological, and treatment characteristics of metastatic MSO, while also investigate the overall survival (OS) rate and factors affecting prognosis in this population. Materials and Methods: A total of 79 cases of metastatic MSO were reviewed, including four cases of metastatic MSO from our hospital and 75 cases sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Despite different management strategies, a recent study showed that patients with malignant SO have excellent disease-specific survival rates, whether or not metastases occurred. 8 This was in agreement with previous reports of 89% to 94.3% 10-year survival rates for patients with malignant SO. 17 , 18 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite different management strategies, a recent study showed that patients with malignant SO have excellent disease-specific survival rates, whether or not metastases occurred. 8 This was in agreement with previous reports of 89% to 94.3% 10-year survival rates for patients with malignant SO. 17 , 18 …”
Section: Discussionsupporting
confidence: 93%
“…In a case series and literature review of metastatic malignant SO, Li et al 8 reported that 24% to 50% initially presented with a benign SO, and the time interval ranged from 2 months to 26 years. This adds to the challenge of a timely diagnosis and reinforced the need for regular follow-up even in benign SO.…”
Section: Discussionmentioning
confidence: 99%
“…There are some factors that have been associated with increased risk of aggressive behavior in malignant SO such as struma size greater than 5 cm, presence of more than 50% of proliferating tissue within a teratoma, extra-ovarian spread, adherence to adjacent organs, ascites, age over 55 years, and FIGO (International Federation of Gynecology and Obstetrics) stage IV of ovarian cancer [2,4,14]. The first 2 were present in our case.…”
Section: Discussion/conclusionmentioning
confidence: 63%
“…Although their study included patients with and without metastasis, they did not evaluate risk factors for overall survival (OS). Our previous study found a similar OS rate in patients with MSO (confined to the ovary) and metastatic MSO ( 10 , 11 ). We found that age ≥55 years was a strong risk factor for OS in patients with metastatic MSO but did not find any statistically significant predictive factor for OS in patients with MSO confined to the ovary.…”
Section: Introductionmentioning
confidence: 59%